THE DETERMINANTS OF HOUSEHOLD SAVINGS IN POLAND - Szopiński, Tomasz (Acta Scientiarum Polonorum. Oeconomia, 2017)
The relevant literature provides an array of factors determining the propensity of households to save. There is no unanimity among researchers as to the direction of statistical relationships among some variables such as, e.g. household income, the place of residence or concerns regarding the worsening of financial circumstances, and a household’s propensity to save. The aim of this article is to verify the statistical relationships between the amount of savings of Polish households and their attributes, such as: income, biological type of the family, and the size of the place of residence. The author of the article analyses the responses provided by Polish households with regard to the size of their savings measured as a multiple of their income. The data under analysis were collected during a panel study Diagnoza społeczna 2015 (ang. Social Diagnosis 2015). Higher earnings were accompanied by higher levels of savings. It was more common for households from bigger cities to have higher earnings. Taking into consideration the biological type of the family, childless marriages and people, who lived alone, declared having the highest savings.